Signaling And Scheduling Wimax Gateway Design Based On Resource Reservation Protocol - Mahmoud Ahmad Albawaleez; Kamaruzzaman Seman; Kamarudin Saadan; Khairi Abdulrahim (Indian Journal of Science & Technology, 2024)
Non-Indexed Publication